1995
DOI: 10.1016/0029-7844(95)00307-d
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic estimation of umbilical coiling index and correlation with doppler flow characteristics

Abstract: An intrauterine umbilical coiling index can be determined by ultrasound and correlates well with the actual index at birth. The sonographic umbilical coiling index is related to Doppler flow characteristics in the umbilical vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 9 publications
7
105
2
2
Order By: Relevance
“…The mean aUCI in the present study was comparable to those of the several similar studies in the past: Otsubo et al [2], 0.39 ± 0.03 coils/cm; Degani et al [3], 0.42 ± 0.12 coils/cm; Predanic and Perni [4], 0.403 ± 2SD coils/cm; Perni [5], 0.4 ± 0.1 coils/cm; and de Laat et al [6], 0.3 ± 0.09 coils/cm. Rana and Ebert [7] concluded that hypercoiling is associated with an increased incidence of premature delivery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean aUCI in the present study was comparable to those of the several similar studies in the past: Otsubo et al [2], 0.39 ± 0.03 coils/cm; Degani et al [3], 0.42 ± 0.12 coils/cm; Predanic and Perni [4], 0.403 ± 2SD coils/cm; Perni [5], 0.4 ± 0.1 coils/cm; and de Laat et al [6], 0.3 ± 0.09 coils/cm. Rana and Ebert [7] concluded that hypercoiling is associated with an increased incidence of premature delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Degani et al [3] concluded that the best single predictor of a small for gestational age infant was the coiling index with sensitivity of 79 %, specificity of 86.5 %, positive predictive value of 72 % and a negative predictive value of 905. Another observation in this study was that both hypercoiling and hypocoiling were significantly associated with low Apgar score as compared with normocoiling.…”
Section: Discussionmentioning
confidence: 99%
“…7 This report indicated that possible reduction of umbilical cord supportive tissue, together in combination with fetal movements in the SGA fetuses, could cause increased cord coiling with advancing gestation. 7,8 In consideration of the possible reduced umbilical cord supportive tissue (thinner cords) involvement in the etiology of umbilical cord coiling, we hypothesized that aUCI should have a significant relationship with the umbilical cord thickness. Therefore, altered umbilical cord thickness may predispose the fetus to the umbilical coiling pattern 7 and possibly may hinder full fetal intrauterine growth potential.…”
mentioning
confidence: 99%
“…Umbilical cord-other (n = 21) and placental abruption (n = 10) were the most common of the 48 second ReCoDes for FGR. To assess umbilical coiling, the umbilical coiling index (UCI) can be measured by ultrasound (Degani et al, 1995), but the sensitivity of the UCI for detection of hypercoiled cord at birth is only 17.3-25.4% (Quin et al, 2002;Predanic et al, 2005) and this method requires further development before it can be reliably used clinically to assess hypercoiled cord in utero.…”
Section: Discussionmentioning
confidence: 99%